Online Learning Collaborative to Increase Knowledge and Skills of Prospective Mathematics Teachers - Buaddin Hasan; Enny Listiawati (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Online learning collaborative as a form of technological transformation in the world of education in higher education. Providing opportunities for students to obtain the broadest possible knowledge and increasing student competencies as a learning outcome as well as providing opportunities for students to develop competencies by studying outside of higher education through a collaborative, collective approach, utilizing science and technology. This research aims to determine the effectiveness and increase the knowledge and skills of prospective mathematics teachers using a online learning collaborative system. Researchers used quantitative methods with a descriptive quantitative approach. The subjects in this research were 19 prospective mathematics teacher from different universities who studied collaboratively using a learning management system. Data analysis was carried out using multiple linear regression. The research results show that the implementation of online learning collaborative has a significant positive impact on increasing the knowledge and skills of prospective mathematics teacher. Students can solve the problems given, and students are skilled in applying information technology in learning. To support effective online learning collaborative, can use learning object materials in the form of learning videos, material slides, infographic media, live chat discussions and interactive games.